DEPRESSION, ANXIETY AND STRESS AS DETERMINANTS OF PROCRASTINATION IN JUNIOR KARATEKAS - Miroljub Ivanović,; Uglješa Ivanović, (Sport Scientific And Practical Aspects, 2025)
The aim of the conducted research was to examine the contribution of predictor variables (depression, anxiety and stress) in predicting the criterion procrastination. The pertinent sample of adolescents (N =126) included junior karatekas age 16 to 18 (M = 17.5, SD = .83). Two measuring instruments were used: General Procrastination Scale (Lay, 1986) and Depression, Anxiety and Stress Scale (Lovibond & Lovibond, 1995).Correlation analysis has determined that there are statistically significant and positive linear connections between the dimensions of psychological distress. The model of hierarchical regression has revealed that the predictor group of variables (depression, anxiety and stress) accounts for 12% of the total criterion variance of procrastination. Only the determinant depression (ß = .41, p ≤ .01) had the maximum positive and statistically relevant partial contribution in predicting the variability of procrastination. The calculated beta coefficient indicates that a higher degree of depression in adolescent karatekas intensifies their procrastination. On the other hand, regression has shown that the independent variables anxiety and stress do not significantly interact with the criterion, and therefore cannot statistically significantly predict the dependent variable procrastination in adolescent karatekas. The obtained results of the constructs examined in this research have theoretical and practical implications in explaining procrastination in adolescent karatekas